Back Cover: Gene Expression Profiling of 1α, 25(OH)2D3 Treatment in 2D/3D Human Hepatocyte Models Reveals CYP3A4 Induction but Minor Changes in Other Xenobiotic‐Metabolizing Genes. Issue 9 (5th May 2022) - Pavek, Petr; Dusek, Jan; Smutny, Tomas; Lochman, Lukas; Kucera, Radim; Skoda, Josef; Smutna, Lucie; Kamaraj, Rajamanikkam; Soucek, Pavel; Vrzal, Radim; Dvorak, Zdenek
Abstract : Mol. Nutr. Food Res . 2022, 66, 202200070 DOI: 10.1002/mnfr.202200070 Few enzymes providing drug clearance are found under the control of activated vitamin D receptor (VDR) in the liver. In article number 2200070, Petr Pavek and co‐workers investigate whether active vitamin D3 regulates major detoxification enzymes and transporters in 2D and 3D cultures of human hepatocytes. They show that VDR or vitamin D supplementation is unlikely to significantly influence drug elimination.